(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
The study examines the interconnection between oral microflora composition and colonization resistance in patients with inflammatory periodontal diseases associated with gastrointestinal disorders. Quantitative and qualitative microbiological analyses were performed on samples collected from various oral biotopes, including the gums, tongue, cheeks, and palate. The findings reveal a significant decrease in resident microorganisms, such as Lactobacillus and Streptococcus, and an increase in opportunistic pathogens, including Candida spp., Klebsiella, and E. coli. The alterations in the oral microbial landscape are linked to systemic changes driven by gastrointestinal pathologies, contributing to the severity of periodontal inflammation. These data provide evidence for the role of systemic factors in modulating oral microbial homeostasis and highlight the need for integrated diagnostic and therapeutic strategies in clinical practice.